KRITIK NABI MIKHA TERHADAP NEPOTISME: PERSPEKTIF HERMENEUTIKA TEOLOGI KEADILAN SOSIAL - Saut Maruli P. Panggabean; Regueli Daeli; Iman Kristina Halawa (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2025)
This article examines the Prophet Micah’s critique of nepotism through the lens of social justice theological hermeneutics. The historical background of eighth-century BCE Judah reveals systemic abuses of power, land confiscation, and political patronage that undermined the social order. Micah exposes this corruption through sharp prophetic rhetoric, portraying leaders as betrayers of their divine mandate. This analysis finds that modern nepotism shares structural similarities with the injustices of Micah’s era, namely the erosion of meritocracy and the weakening of social solidarity. The novelty of this research lies in positioning nepotism as an independent theological category within the interpretation of the Book of Micah. The research results affirm that the struggle against nepotism encompasses three crucial dimensions: (1) as an ethical agenda in social life; (2) as a prophetic calling to embody God's justice (mishpat) in the public sphere; and (3) as a theological calling to restore the integrity of public spirituality centered on faith loyalty and the rejection of exclusive privileges. Consequently, this article grounds Micah's message as an instrument of socio-political transformation relevant to the context of modern leadership in Indonesia.